Gambaran Status Gizi & Kadar Hemoglobin Pada Remaja Putri di YPM Diponegoro - Kaltim, Brinda; Astutik, Widya; Sulistyorini, Chandra (Jurnal Inovasi Global, 2025)
Adolescents are an age group that is prone to experiencing malnutrition problems or more. Nutritional status is a measure of a person's body condition which can be seen from the food consumed and the use of nutrients in the body lack of nutrients causes Hb levels to continue to decrease and cause anemia, Anemia is a condition where Hb is lower than normal, normal Hb levels for adolescent girls are ≥12 g/dL. According to Riskesdas data in 2018, the prevalence of anemia was around 32% in adolescents with an age range of 15-24 years in 2018. Objective: This study is to find out the description of nutritional status and hemoglobin levels in adolescent girls at YPM Diponegora High School. Method: This study uses a descriptive research design. The population is all young women in classes X and XI at YPM Diponegora High School as many as 76 respondents. Data collection technique using random sampling techniques. The data analysis used in this study is Univariate analysis. Results: adolescents aged 16 - 17 years 24 female students (55.8%). 8 students (18.6%) had a poor nutritional status, 7 students had an obese nutritional status (16.3%), and 26 students had a normal nutritional status (60.5%). Hemogelobin levels were 9 students with mild anemia (20.9%), 32 female students (74.4%) Normal. Conclusion: Based on the tabulation, age characteristics, nutritional status, and hemoglobin levels in adolescent girls of YPM Diponegoro High School, most of the respondents were included in the category of normal nutritional status, and were not anemic.